Encouraging regional accountability in the supply and distribution of renewable electricity - Rooney, Sophie (2016)
Traditional methods of electricity generation and distribution within the UK have developed around the notion of a highly centralised system, based on the extensive use of fossil fuels. These fuels present a number of challenges; including the depletion of resources, negative environmental impacts, socio-economic barriers and political obstructions. As a result, the development and integration of renewable technologies is imperative in the creation of an energy system which is fully sustainable in the long term. This study investigates the level of planned renewable infrastructure in the UK and the likely increase in electrical generation capacity which will result from the completion of all planned projects. The regional distribution of this generation is explored, in addition to the proportion of electricity demand within each region which can be met by renewable sources of generation under a variety of future scenarios. Overall, there is a high level of variation in the proportion of electricity demand which can be met through renewable generation in each region, with two regions (Yorkshire and Scotland) displaying sufficient planned infrastructure to meet greater than 100% of future energy demand, whilst other regions illustrate low levels of increased generation - the lowest of which is seen in the London region, where a maximum of 3% of electricity demand is estimated to be met through renewable generation in the future. Overall, it is suggested that encouraging regional accountability for the supply and distribution of renewable electricity will enable increased sustainability and efficiencies in the energy system, and increase the likelihood of establishing a fully sustainable energy system in the UK in the future